Juridical Analysis Of The Dismissal Of Constitutional Judges By The House Of Representatives In Review Of Law No. 7 Of 2020 Concerning The Constitutional Court From Maslahah Perspective - Amri Wahyudi; Cholidi Cholidi; Cholidah Utama (Journal of Research in Social Science and Humanities, 2025)
The dismissal of a Constitutional Court justice by the Indonesian House of Representatives has generated constitutional and legal debate, particularly regarding the separation of powers and judicial independence. According to Law Number 7 of 2020, such dismissal must follow a clearly defined legal procedure. However, the DPR’s removal of Justice Aswanto without proper legal justification is widely considered to be in violation of applicable laws. Viewed through the lens of maslahah—a foundational principle in Islamic law—this action fails to promote public benefit (maslahah ‘ammah) and instead poses a risk of harm (mafsadah) to judicial legitimacy and public justice. Thus, this issue serves as a relevant case to examine whether a public policy aligns with both constitutional standards and the moral-religious values of Islamic legal theory.